Brief Report: An Open-Label Study of the Neurosteroid Pregnenolone in Adults with Autism Spectrum Disorder - Fung, Lawrence K.; Libove, Robin A.; Phillips, Jennifer; Haddad, Francois; Hardan, Antonio Y. (Journal of autism and developmental disorders, 2014)
The objective of this study was to assess the tolerability and efficacy of pregnenolone in reducing irritability in adults with autism spectrum disorder (ASD). This was a pilot, open-label, 12-week trial that included twelve subjects with a mean age of 22.5 ± 5.8 years. Two participants dropped out of the study due to reasons unrelated to adverse effects. Pregnenolone yielded a statistically significant improvement in the primary measure, Aberrant Behavior Checklist (ABC)-Irritability [from 17.4 ± 7.4 at baseline to 11.2 ± 7.0 at 12 weeks ( p = 0.028)]. Secondary measures were not statistically significant with the exception of ABC-lethargy ( p = 0.046) and total Short Sensory Profile score ( p = 0.009). No significant vital sign changes occurred during this study. Pregnenolone was not associated with any severe side effects. Single episodes of tiredness, diarrhea and depressive affect that could be related to pregnenolone were reported. Overall, pregnenolone was modestly effective and well-tolerated in individuals with ASD.